Dietitian visits were a safe and cost‐effective form of follow‐up care for children with celiac disease. (2nd July 2018) - Johansson, Karolina; Malmberg Hård af Segerstad, Elin; Mårtensson, Helena; Agardh, Daniel
Abstract: Aim: This study compared follow‐up protocols for paediatric celiac disease (CD) led by either paediatricians or dietitians at Swedish university hospitals. Methods: We followed 363 CD patients under 18 years at the university hospitals in Malmö (n = 140) and Lund (n = 79) between 2011 and 2013 and after they merged to become Skåne (n = 144) between 2014 and 2016. Both Lund and Malmö provided regular paediatrician follow‐up visits, whereas Skåne provided mainly dietitian‐led visits. Results: Children at Lund were followed for a mean of 1.0 ± 0.5 visits per year, compared to 0.7 ± 0.6 at Malmö (p < 0.0001) and 0.9 ± 0.6 at Skåne (p = 0.11). The ratio of annual paediatrician to dietitian annual visits was 1.4:1.0 at Lund, which was higher than Malmö (0.9:1.0; p = 0.0017) and Skåne (0.6:1.0; p < 0.0001). There was no difference in the prevalence of non‐compliant patients between the clinics (p = 0.26, Malmö 13.6%, Lund 10.1%, Skåne 7.6%). Tissue transglutaminase autoantibody levels reversed equally over time at all three clinics after the subjects started a gluten‐free diet (r = −0.55, p < 0.0001). The total mean annual cost per patient was lowest at Malmö and highest at Lund (p < 0.0001). Conclusion: Dietary compliance was similar regardless of whether care was provided by a dietitian or paediatrician. Dietitian‐led follow‐up visits may provide lower long‐term costs. Abstract :